Investigation of mechanicaland structural characteristics of some alloys in Ag-rich corner of Ag-Cu-Sn system - Marjanović S.; Gusković D.; Trucić M.; Marjanović B. (Journal of Mining and Metallurgy. Section B: Metallurgy)
Results of investigation of mechanical and structural characteristics of some Ag-rich alloys in Ag- Cu-Sn system are presented in this paper. Starting samples were four small billets with different contents of constituting elements - Ag90Cu5Sn5, Ag85Cu5Sn10, Ag85Cu10Sn5, Ag80Cu10Sn10 (at%), prepared from p.a. metals Sn, Ag, Cu by melting in electro-inductive furnace under air atmosphere and additional reductant and cast into bars of square shape, dimensions 1x1x10cm. Mechanical characteristics, such as hardness and microhardness, electroconductivity and microstructure, were observed before and after a series of passes through a grooved roll stand (cold rolling).